Analisis Klasifikasi Perfomance KPI Salesman Menggunakan Metode Decision Tree Dan Naïve Bayes - Seanand Sonia Shabrilianti; Agung Triayudi; Dhieka Avrilia Lantana (JURIKOM (Jurnal Riset Komputer), 2023)
Along with the rapid and innovative development of technology, it has a big influence, especially for large companies. Unlike today, employees still use manual methods, as in determining the results of the achievement of the salesman. With the existence of technology can help various forms of problems in work, Making it easier to work with in a possibly short period of time makes time more efficient. This study aims to improve the performance of company employees who are prioritized to do work with the help of technology,  or rather on a system so that it no longer does the work manually, also helps the company develop more with the existence of technology that will continue to be new. This study also aims to test the results of the level of accuracy using two methods, in order to find the best between the two methods on the data of the results of achieving salesman KPI. By using two methods, namely the decision tree method and naïve bayes. The classification of these two methods can test the results of how high the accuracy results are based on the processed data. Using more than one method to find which method is more influential, and better in those classifications. The results of this study show that the decision tree method got very good results in this study because it produced perfect accuracy, reached the 100% mark whereas by the naïve bayes method it was only 41%.